An Improved Image Watermarking Using LTVC Scheme (International Journal of Engineering and Computer Science, 2017)
Security has gained a lot of importance as information technology is widely used. The main issue in visual cryptography is quality of reconstructed image. This problem is overcome by using “An improved image watermarking using LTVC scheme”. In this method the quality of reconstructed image is higher, compare with conventional visual cryptographic scheme. The secret image is converted into shares, that means black and white pixel images. Each share is embedded to different carrier images. Invisible watermarking method is used for embedding carrier image and shares. For security, the invisible watermarked shares are then encrypted, AES modified encryption method is used. The encrypted shares are send to other participants. At the receiver end receiving the shares and decrypt the shares, then combining these shares together reveal the secret. The quality of rejoined shares and original secret shares are almost same. The loss of image quality is less compared to other visual cryptographic schemes.